An integrated Taguchi and response surface methodological approach for the optimization of an HPLC method to determine glimepiride in a supersaturatable self-nanoemulsifying formulation - Rajendra Narayan Dash; Habibuddin Mohammed; Touseef Humaira (Elsevier, 2016)
We studied the application of Taguchi orthogonal array (TOA) design during the development of an isocratic stability indicating HPLC method for glimepiride as per TOA design; twenty-seven experiments were conducted by varying six chromatographic factors. Percentage of organic phase was the most significant (p < 0.001) on retention time, while buffer pH had the most significant (p < 0.001) effect on tailing factor and theoretical plates. TOA design has shortcoming, which identifies the only linear effect, while ignoring the quadratic and interaction effects. Hence, a response surface model for each response was created including the linear, quadratic and interaction terms. The developed models for each response found to be well predictive bearing an acceptable adjusted correlation coefficient (0.9152 for retention time, 0.8985 for tailing factor and 0.8679 for theoretical plates). The models were found to be significant (p < 0.001) having a high F value for each response (15.76 for retention time, 13.12 for tailing factor and 9.99 for theoretical plates). The optimal chromatographic condition uses acetonitrile - potassium dihydrogen phosphate (pH 4.0; 30 mM) (50:50, v/v) as the mobile phase. The temperature, flow rate and injection volume were selected as 35 ± 2 °C, 1.0 mL min−1 and 20 μL respectively. The method was validated as per ICH guidelines and was found to be specific for analyzing glimepiride from a novel supersaturatable self-nanoemulsifying formulation. Keywords: Taguchi orthogonal array, Signal-to-noise ratio, Response surface methodology, S-SNEDDS, Optimization, HPLC method